(untitled) (Medical Forum Monthly, 2025)
Objective: This study was to assess the diagnostic value of hematological parameters in predicting disease activity of SLE with SLEDAI as the reference standard. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Dr. Ruth K.M Pfau Civil Hospital, Karachi from February to July 2023. Methods: This study was performed on 40 SLE patients. In this study Disease activity was evaluated by SLEDAI, and the association between SLEDAI and complete blood count (CBC)-based indicators (neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR)), erythrocyte sedimentation rate (ESR), complement proteins (C3/C4) and antinuclear antibody (ANA) levels were studied. Statistical methods involved use of Shapiro-Wilk tests for normality, Spearman’s rank correlation, chi-square tests, and Kruskal-Wallis test. Results: ANA levels and SLEDAI scores showed a weak but statistically significant positive connection (r = 0.318, p = 0.045), indicating limited usefulness in monitoring disease activity. SLEDAI, on the other hand, did not significantly correlate with CBC-derived inflammatory indices, such as the neutrophil-to-lymphocyte ratio (NLR; p = 0.590) or the platelet-to-lymphocyte ratio (PLR; p = 0.103). Likewise, there was no statistically significant association between disease activity scores and complement protein levels (C3: p = 0.566; C4: p = 0.180) or erythrocyte sedimentation rate (ESR; p = 0.230). With higher SLEDAI classifications, the prevalence of anemia seemed to rise quantitatively; nevertheless, this trend fell short of statistical significance (p = 0.575). Additionally, categorical analyses revealed no significant associations between SLEDAI-defined disease severity and gender, treatment-naïve status, or the presence of hepatosplenomegaly (p > 0.05 for all). Shapiro-Wilk testing confirmed non-normal distributions for both ANA and SLEDAI scores, necessitating the use of non-parametric statistical methods for analysis. Conclusion: Hematological parameters (NLR, PLR, ESR) and routine biomarkers (C3/C4) demonstrated limited reliability as standalone indicators of SLE activity in this resource-constrained cohort. While ANA showed modest correlation, its variability limits clinical utility. The findings highlight the complexity of SLE monitoring and underscore the need for integrated, context-specific approaches combining clinical assessment with accessible biomarkers. Further validation of cost-effective composite tools is critical for low-resource settings where advanced diagnostics remain unavailable.